PENGARUH BIMBINGAN KELOMPOK TERHADAP KECANDUAN GADGET SISWA DI SMAN 1 KAMPAR TIMUR - Rini Kurnia; Tri Umari; Donal Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine the level of gadget addiction before and after the guidance group implementation and to determine the effect of group counseling on the level of gadget addiction in students at SMAN 1 Kampar Timur. This research method uses a pre-experimental design method. With the type of research one group pretest-posttest pre-experimental design. The type of one group pretest-posttest (pre-test-posttest single group) is giving the test before the experiment once (pre-test) and giving the test once (post-test). Data collection techniques in this study used questionnaires, interviews, and observations. The research subjects were determined by purposive sampling technique, namely 7 students who had a high gadget addiction in class XI Social Sciences who were obtained from questionnaire data management and then were given group guidance services for 6 meetings. The conclusions in this study were as follows: (1) before the implementation of the gadget addiction group guidance service, some students were in the high category and after being given the gadget addiction group guidance service, most of the students were in the low category (2) There were differences in student gadget addiction before and after the implementation of the service guidance group (3) There is the influence of group guidance groups to reduce students' gadget addiction Key Words: Gadget Addiction, Counseling.